A Multidisciplinary Approach to Health Prevention with the Emphasis on Multimorbidity in Post Conflict Serbia – Results of the Qualitative Research - Mladenović, Aleksandra; Matijević, Branka; Sjeničić, Marta (Medicine, Law & Society, 2022)
In the period 2019-2021, the Serbian team (consisted form representatives of the Institute for Biological Research "Siniša Stanković", Institute of Public Health of Serbia "Dr Milan Jovanović Batut", Environmental Protection Agency, the Medical Faculty in Belgrade, Ministry of Health and the Institute of Social Sciences) conducted the research project on health prevention and multimorbidity in post conflict Serbia. Objective was to understand the perception of relevant actors about possible risk factors (environmental, behavioral, and socio-economic) for the occurrence of multimorbidity. Methodology applied in qualitative research was focus groups and interviews with the sampled population group representatives. Target population was health professionals, health providers’ and local municipalities’ management. The purposes of the research were: 1) insight into the main multimorbidity factors through the prism of stakeholders on the local level; 2) drafting recommendations on changing regulation and practice in public health prevention measures. Results of the research show that there is an agreement in the stakeholder perception that multimorbidity in Serbia is increasing and that preventive measures should be strengthened. All groups of predictors (environmental, behavioral, and socio-economic) are perceived as of equal importance. The research was the basis for development of the legislative and systemic recommendations.